The ligamentum mucosum’s potential as a preventative structure in the development of knee osteoarthritis - Alexandra Martin; Kenneth Liu; Majid Alimohammadi (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose This paper aimed to identify whether the presence, type, and/or morphology of the ligamentum mucosum could play a role in the development of knee osteoarthritis. Since its microscopic structure is alike that of other knee ligaments, it was hypothesized that its presence could facilitate knee motion and stability, thus preventing or reducing the extent of knee osteoarthritis. Methods Thirty three cadavers (a total of 51 knees) were dissected. The ligamentum mucosum, if present, was measured with a digital caliber and a measuring tape in terms of length, width, and thickness. Knee osteoarthritis was assessed in six regions of the knee. The OuterBridge Classification System (Grades 0–4) was used to visually assess the extent, in addition to probing the area. Osteoarthritis was deemed present if the grade was 2 or greater. Results The presence of the ligament was associated with a lower mean osteoarthritis level in the trochlear groove and lateral tibial plateau regions (p < 0.001 and p = 0.013, respectively). Overall osteoarthritis of the knee was also present at varying levels for each type of the ligamentum mucosum (p < 0.001). The patella and the medial condyle had the greatest levels of osteoarthritis, while the medial and lateral tibial plateaus had the lowest levels. Conclusion The presence of the ligamentum mucosum is linked with decreased osteoarthritis in the trochlear groove region. In addition, both the absent ligament and its classification as a vertical septum are associated with increased knee osteoarthritis. Level of evidence Five.